The influence of duration and level on human sound localization - Vliegen, Joyce; Van Opstal, A John (The Journal of the Acoustical Society of America, 2004)
The localization of sounds in the vertical plane (elevation) deteriorates for short-duration wideband sounds at moderate to high intensities. The effect is described by a systematic decrease of the elevation gain (slope of stimulus-response relation) at short sound durations. Two hypotheses have been proposed to explain this finding. Either the sound localization system integrates over a time window that is too short to accurately extract the spectral localization cues (neural integration hypothesis), or the effect results from cochlear saturation at high intensities (adaptation hypothesis). While the neural integration model predicts that elevation gain is independent of sound level, the adaptation hypothesis holds that low elevation gains for short-duration sounds are only obtained at high intensities. Here, these predictions are tested over a larger range of stimulus parameters than has been done so far. Subjects responded with rapid head movements to noise bursts in the two-dimensional frontal space. Stimulus durations ranged from 3 to 100 ms; sound levels from 26 to 73 dB SPL. Results show that the elevation gain decreases for short noise bursts at all sound levels, a finding that supports the integration model. On the other hand, the short-duration gain also decreases at high sound levels, which is in line with the adaptation hypothesis. The finding that elevation gain was a nonmonotonic function of sound level for all sound durations, however, is predicted by neither model. It is concluded that both mechanisms underlie the elevation gain effect and a conceptual model is proposed to reconcile these findings.